Epidemiological trends and novel prognostic evaluation approaches of patients with stage II-IV colorectal neuroendocrine neoplasms: A population-based study with external validation - Zhao, Fuqiang; Huang, Liling; Wang, Zhijie; Wei, Fangze; Xiao, Tixian; Liu, Qian (Frontiers in Endocrinology, 2023)
Objective: This study aimed to clarify the incidence trend of all stage colorectal neuroendocrine neoplasms (CRNENs), overall survival (OS), and disease-specific survival (DSS) of patients with stage II-IV CRNENs, and to establish relevant nomograms for risk stratification. Methods: CRNENs in the Surveillance, Epidemiology, and End Results (SEER) database from 1975 to 2019, temporal trends in incidence was assessed. Clinical data of 668 patients with stage II-IV CRNENs from 2010 to 2016 were extracted for survival analysis. Patients were randomly divided into training cohort and validation cohort at a ratio of 7:3. Univariate and multivariate cox regression analysis were utilized to identify independent prognostic factors affecting OS outcomes. Competing risk analysis was applied to investigate risk factors related to DSS of CRNENs. Two nomograms specifically for OS and DSS were developed for patients with stage II-IV CRNENs, their prognostic capabilities were evaluated using calibration curves, receiver operating characteristic (ROC) curves, time-dependent area under the curve (AUC), and decision-curve analysis (DCA). Results: In total, 668 patients with stage II-IV CRNENs were included in the survival analysis from 2010 and 2016. Independent adverse prognostic factors for both OS and DSS of CRNENs prior treatment included grade III/IV, higher TNM stage, liver metastasis, and brain metastasis. Advanced age was also identified as a risk factor for OS but not DSS. In terms of treatment, surgery can significantly prolong OS and DSS , but chemotherapy and radiation failed to show significance. The respective nomograms for OS and DSS for stage II-IV CRNENs demonstrated high accuracy and robust prediction value in predict 1-year, 3-year, and 5-year OS and DSS outcomes in training, internal validation, and external validation cohorts. Conclusion: Over the past 40 years, the incidence of CRNENs presented increased steadily, along with improved survival outcome. Grade III-IV, higher TNM stage, liver metastasis, brain metastasis, and without receiving surgery were found to be associated with worse OS and DSS. Advanced age was a risk factor of OS but not DSS. Nomograms for patients with stage II-IV stage CRNENs are capable of predicting the 1-, 3-, and 5-year OS and DSS rates with high accuracy.